2021
DOI: 10.31106/jema.v18i1.9235
|View full text |Cite
|
Sign up to set email alerts
|

How does the impact of the COVID-19 pandemic on Indonesia's Islamic stock returns?

Abstract: The unprecedented COVID-19 pandemic has ripped down the worldwide economies since the beginning of 2020. The stock market was one of the economic sectors that experienced depression and crashed during the pandemic. In this study, we mount an investigation on how Indonesia's large-scale social restrictions (known as "PSBB"), the announcement of the daily growth in total confirmed and death cases by COVID-19 affect the dynamic of Islamic stock returns in the Jakarta Islamic Index. This study used panel regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Agustin [51] explored the impact of rising cases and deaths due to COVID-19 along with the implementation of social restrictions on the performance of the Islamic stocks listed under the Indonesia Stock Exchange. Panel regression was applied to the daily stock price of the companies listed under the Jakarta Islamic Index from December 2019 to November 2020.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Agustin [51] explored the impact of rising cases and deaths due to COVID-19 along with the implementation of social restrictions on the performance of the Islamic stocks listed under the Indonesia Stock Exchange. Panel regression was applied to the daily stock price of the companies listed under the Jakarta Islamic Index from December 2019 to November 2020.…”
Section: Related Workmentioning
confidence: 99%
“… [48] Stock price volatility and revenue shock for S&P 500 stocks Event study Kumar and Kumara [49] Performance of NIFTY 50 (India) before and after the pandemic (Period: January, April & June 2020) Descriptive analysis and time series modelling Sun et al. [50] Investigation on investors’ sentiments and stock market reaction in terms of price movement and volatility in Chinese market (Period: 25th July 2019 to 31st March 2020) Event study and panel regression Agustin [51] Performance of the Islamic stocks listed under the Indonesia Stock Exchange using daily stock prices (period: December 2019 to November 2020) Panel regression Bing [52] Relationship between the retail investor’s behaviour and their ability to forecast the market during the COVID-19 in Chinese stock market (Period: January 2019 to March 2020) Bivariate Vector Auto Regression Model Kusumahadi and Permana [53] The impact of COVID-19 on the volatility of stock returns of 15 countries using daily data from January 2019 to June 2020 Generalised Autoregressive Conditional Heteroskedasticity Regression Yong et al. [54] Analyze the stock volatility and performance before and during the COVID-19 pandemic using the daily closing prices of indices for FTSE Malaysia KLCI Index and FTSE Straits Time Index.…”
Section: Related Workmentioning
confidence: 99%
“…On March 11, 2020, the World Health Organization declared coronavirus disease (COVID-19) as a global pandemic (Nurcahyono et al, 2021). In response to this public health emergency, the Indonesian government implemented large-scale social restrictions (Agustin, 2021), resulting in significant economic impacts both domestically and globally (Agustin, 2021). Job losses, business downturns, and increased healthcare expenditures by governments became prevalent as measures to combat the pandemic (Albaity et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have shown that the COVID-19 pandemic has adversely affected stock markets. Prior literature indicates that information related to COVID-19 significantly influences stock market prices (Al-Awadhi et al, 2020;Ashraf, 2020;Akhtaruzzaman et al, 2020;Albulescu, 2021;Agustin, 2021). This impact is attributed to the typical responsiveness of stock returns to market events (Robin, 2021) and economic shocks such as natural disasters and political events (Insaidoo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Lockdown, quarantine, and isolation as a result of the incessant escalation of the pandemic caused people to feel anxious, and consider themselves to be at risk of COVID-19 (Yıldırım & Güler, 2020). The deepening multiple pandemic effects in many countries has resulted in a general trend of increasingly restrictive policies toward many aspects of society (Agustin, 2021;Tahar et al, 2021). It brings an increasing understanding of risk, as evidenced by several recent studies reviewing the perceived risk of COVID-19 that is experienced by people in several regions of the world (Dryhurst et al, 2020;Huynh, 2020).…”
Section: Introductionmentioning
confidence: 99%